Causes of death in the decade after hospitalisation for injury during adolescence: a study using linked hospital admissions and death registrations data - Annie Herbert; Ruth Gilbert; David J Cottrell; Arturo Gonzalez-Izquierdo; Leah Li (International Journal of Population Data Science, 2017)
ABSTRACT